Estrogen valerate pretreatment with the antagonist protocol does not increase oocyte retrieval in patients with low ovarian response: a randomized controlled trial. Issue 7 (23rd April 2022) - Zhang, Shunji; Tang, Yi; Wang, Xiaojuan; Zong, Yurong; Li, Xiaofeng; Cai, Sufen; Ma, Hailan; Guo, Hui; Song, Juan; Lin, Ge; Lu, Guangxiu; Gong, Fei
Abstract: STUDY QUESTION: Does luteal phase estrogen valerate pretreatment improve oocyte yield and clinical outcomes in patients with low ovarian response during ovarian stimulation with the antagonist protocol? SUMMARY ANSWER: Pretreatment with oral estrogen valerate from Day 7 after ovulation to Day 2 of the next menstrual cycle did not increase oocyte yield in patients with a low ovarian response compared to no pretreatment. WHAT IS KNOWN ALREADY: Previous studies showed that patients with a normal ovarian response can obtain better clinical outcomes after pretreatment with estrogen in the antagonist protocol. For patients with advanced age and low ovarian response, it remains unclear if estrogen valerate pretreatment with the antagonist protocol yields more oocytes and improves pregnancy outcomes. STUDY DESIGN, SIZE, DURATION: This non-blinded randomized controlled trial (RCT) was conducted between November 2017 and March 2021. Participants were 552 women with low response who requested IVF treatment. The primary endpoint was comparison of the total number of retrieved oocytes between the two groups. The secondary endpoints were the total number of retrieved metaphase II (MII) oocytes, duration and total dosage of recombinant FSH (rFSH), good-quality embryo rate and clinical pregnancy rate. PARTICIPANTS/MATERIALS, SETTING, METHODS: The study was conducted at a reproductive center. The RCT enrolled 552 infertile women with a low ovarian response (according to the Bologna criteria) who were undergoing IVF. In the study group, on Day 7 after ovulation patients were administered oral estrogen valerate (2 mg twice a day) until Day 2 of their next menstruation. Ovary stimulation was performed using rFSH, and a GnRH antagonist (0.25 mg/day) was started when a dominant follicle had a mean diameter ≥13 mm. MAIN RESULTS AND THE ROLE OF CHANCE: No significant difference was observed in the number (mean [SD]) of oocytes retrieved from the estrogen valerate pretreatment and control group (3.2 [2.8] versus 3.4 [2.6], respectively). The treatment difference was −0.18 (95% CI −0.67, 0.32, P  = 0.49). No significant differences were observed in the number of MII oocytes (2.9 [2.5] versus 3.1 [2.4], mean difference −0.23, 95% CI (−0.69, 0.23), P  = 0.16) and good-quality embryos (1.0 [1.3] versus 1.20 [1.6], mean difference −0.23, 95% CI (−0.50, 0.04), P  = 0.19) between the two groups. The duration of rFSH treatment was significantly longer in the estrogen valerate pretreatment group than in the control group (10.3 [2.2] versus 8.6 [2.1] days, mean difference 1.7, 95% CI (1.3, 2.2), P  = 0.00), and the total rFSH dosage was significantly higher in the estrogen valerate pretreatment group than in the control group (3081 [680] versus 2548 [649] IU, mean difference 553.7, 95% CI (405.8, 661.6), P  = 0.00). The clinical pregnancy rate in the pretreatment group (19.3% [23/119]) was not significantly different from that in the control group (28.7% [43/150]). The mean difference was −0.09, 95% CI (−0.20, 0.01), P  = 0.08. LIMITATIONS, REASONS FOR CAUTION: The major limitation was the high dropout rate of patients. Some patients did not return to the hospital for treatment because of predicted low success rates and for economic reasons. In addition, it is possible that the fixed dose of 300 IU rFSH was not sufficient to see differences in oocyte yield between the groups. WIDER IMPLICATIONS OF THE FINDINGS: Estrogen valerate pretreatment with an antagonist protocol did not increase oocyte yield in patients with low ovarian response. Similar to the number of retrieved oocytes, there was no significant difference in clinical pregnancy rate between estrogen pretreatment group and control group. More research is needed on whether patients with low ovarian response need pretreatment and which pretreatment is more appropriate. STUDY FUNDING/COMPETING INTEREST(S): This study was supported in part by a research grant from the Investigator-Initiated Studies Program of MSD (China) Holding Co., Ltd. and Organon (Shanghai) Pharmaceutical Technology Co., Ltd. (Grant number: IIS 56284). The authors declare that they have no competing interests regarding authorship or publication of this study. TRIAL REGISTRATION NUMBER: ClinicalTrials.gov NCT03300518. TRIAL REGISTRATION DATE: 28 September 2017. DATE OF FIRST PATIENT'S ENROLMENT: 15 November 2017.